Sardinia Radio Telescope structural behavior under solar thermal load. (May 2022) - Attoli, Alessandro; Stochino, Flavio; Buffa, Franco; Poppi, Sergio; Serra, Giampaolo; Sanna, Giannina; Cazzani, Antonio
Abstract: Sardinia Radio Telescope (SRT) with its 64 m diameter primary mirror is a modern radio-astronomic facility. Its large dimensions allow to reach high performances, but, at the same time, make the antenna sensitive to deformations caused by environmental factors such as gravity, wind and temperature changes. Indeed, it is important to determine the effects that environmental loads produce on this structure. In this paper, the SRT pointing error variation produced by solar radiation acting on its structural system has been studied. Through a sensitivity analysis it was possible to establish that the Alidade is the radio telescope component that produces higher pointing errors when subjected to thermal load. Then, an analytical model was used to estimate the temperature of the Alidade trusses exposed to solar radiation. Furthermore, the calibration of the analytical model parameters was performed by comparing the experimental data obtained by thermographic investigations. Then, using Finite Element Analysis, the pointing error generated by each simulated thermal scenario was determined. Finally, the numerical results allow to better understand the structural behavior of SRT in realistic thermal conditions.